The Effect of Tax Knowledge, Taxpayer Awareness, Education Level, Tax Socialization and Tax Justice on Taxpayer Compliance for SMEs (Study On Convection Taxpayer In Kudus) - Putri APRILIA; ZULIYATI; Zaenal AFIFI (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2022)
This study aims to examine the effect of tax knowledge, taxpayer awareness, education level, tax socialization, and tax justice on taxpayer compliance in UMKM in Kudus. The population in this study is UMKM in Kudus which is engaged in convection. The method in this study used purposive sampling with a total sample of 136 convection units. The type of research used is quantitative research which aims to reveal the truth contained in the research problem that I studied with multiple linear regression testing. The results of this study indicate that tax knowledge and tax socialization have a positive effect on taxpayer compliance for UMKM. This shows that the higher the level of knowledge and socialization of taxation in UMKM taxpayers, UMKM taxpayers are also more obedient to tax regulations. while taxpayer awareness, education level, and tax justice have a negative effect on UMKM taxpayer compliance. This shows that taxpayer awareness, education level, and tax justice do not make UMKM taxpayers obedient to taxation.